The governance of smart cities: A systematic literature review - Ruhlandt, Robert Wilhelm Siegfried (Cities, 2018)
Research on smart cities lacks a systematic understanding of the different components of smart city governance, the metrics to measure these components, their envisaged outcomes and potential contextual factors influencing both components as well as outcomes. This study analyzes the relevant body of literature and proposes conceptual insights. A research scheme is generated and used for an extensive discussion of the literature. The systematic literature review indicates that various smart city governance definitions exist. Also, this study reveals substantial variances in contextual factors, measurement techniques and outcomes among the concepts of smart city governance. •In general, research on smart cities lacks a systematic understanding of the different components of smart city governance.•Therefore, this paper analyzes the relevant body of literature on smart city governance and proposes a systematic understanding of the different components of smart city governance, the metrics to measure these components and their envisaged outcomes.•Thereby, a research scheme is generated and then used for an extensive discussion of the literature.•The systematic literature review indicates that various smart city governance definitions exist, emphasizing on various focal points.•Also, this study reveals substantial variances in contextual factors, measurement techniques and outcomes among the concepts of smart city governance.